Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/copd.s229630
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Everyday Technology Use, Activities of Daily Living and Health-Related Quality of Life in Chronic Obstructive Pulmonary Disease</p>

Abstract: Purpose: A decline in the ability to perform activities of daily living (ADL) and ability to use everyday technology can pose threats to independent living, healthcare management and quality of life (QOL) of patients suffering from chronic obstructive pulmonary disease (COPD). Evidence of the relationship between these variables remains limited. The dual aim of this study was, first, to investigate if health-related QOL (HRQOL) was associated with quality in ADL performance and everyday technology use; second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…In addition, researchers have found that sociodemographic variables, such as age at the time of the survey, gender, medical insurance, socioeconomic, and education level, might affect the psychological outcomes of patients (Kaptain et al., 2020; Stellefson et al., 2019). Therefore, such variables are considered to be the potential sources of confusion and their relationships with hope, meaning in life, and PTG are explored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers have found that sociodemographic variables, such as age at the time of the survey, gender, medical insurance, socioeconomic, and education level, might affect the psychological outcomes of patients (Kaptain et al., 2020; Stellefson et al., 2019). Therefore, such variables are considered to be the potential sources of confusion and their relationships with hope, meaning in life, and PTG are explored.…”
Section: Introductionmentioning
confidence: 99%
“…7 ET is complex to integrate and integration of ET in rehabilitation requires health professionals staying updated and daring to take new challenges; however, focusing on ET makes it possible to support the benefits of digitalization. 7 Since the ability to perform ADL and use ET are associated with health-related quality of life in people living with COPD, 20 it is of critical importance to investigate ADL performance including ET use in order to support the development of interventions that could be integrated in pulmonary rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…1,23 Details of ADL performance are essential in order to be able to address interventions effectively in people living with COPD so as to improve everyday functioning and independence, and thus influence quality of life. 20 Therefore, this study has a twofold aim: 1) to explore observed and self-reported ADL performance, and 2) to investigate the relationship between observation and self-reporting when evaluating ADL performance and between observed/self-reported ADL performance and the ability to use ET in people living with COPD. centres in the Northern Region of Denmark using a convenience sampling procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Welfare Technology is described to have potential to free up resources, giving people the opportunity to better manage healthcare needs, reduce costs, and promote research, development, and innovation [15]. There is also incipient evidence that technology-based interventions promotes instrumental activities of daily living [16], health-related quality of life [17], and mental wellbeing among older people [18]. Strong and early WT initiatives on the verge of being implemented widely include GPS alarms, eating robots, hygiene robots, medicine reminders, and supervision/ (non-intruding) surveillance cameras [19].…”
Section: Introductionmentioning
confidence: 99%